Diets high in n-3 fatty acids are associated with lower arterial stiffness in patients with rheumatoid arthritis: a latent profile analysis. Issue 2 (15th November 2018) - Woodman, Richard J.; Baghdadi, Leena R.; Shanahan, E. Michael; de Silva, Inushi; Hodgson, Jonathan M.; Mangoni, Arduino A.
Abstract: Supplementation with n -3 fatty acids can influence inflammation and markers of arterial stiffness that are increased in patients with rheumatoid arthritis (RA). However, it is unknown whether specific patterns of dietary fatty acid intake are similarly associated. In a longitudinal study, eighty-six RA patients reported their dietary intake and had arterial stiffness measured using the augmentation index (AIx) at baseline and 8 months. Latent profile analysis (LPA) was performed to characterise patterns of fatty acid intake using sixteen major fatty acids. Models for two to six profiles were compared using the Akaike and Bayesian information criteria. Associations between AIx and the profiles were adjusted for age, sex, disease activity, fish oil supplementation, medications, physical activity and socio-economic status. LPA identified five distinct profiles. Profile 1 subjects ( n 7) reported significantly higher intake of palmitoleic acid (16 : 1), arachidonic acid (20 : 4 n -6), EPA (20 : 5 n -3), DHA (22 : 6 n -3) and docosapentaenoic acid (22 : 5 n -3) ( P <0·001 for each) than profiles 2 ( n 14), 3 ( n 19), 4 ( n 23) and 5 ( n 23) and significantly higher grilled and tinned fish consumption. The AIx varied significantly across the five profiles ( P =0·023); subjects in profile 1 had a significantly lower AIx than those in profile 3 ( β =–7·2 %; 95 % CI –11·5, –2·9; P =0·001) who had the lowest reported intake of n -3 fatty acids. Fish oil supplementation was also independently associated with lower AIx ( β =–4·15 %; 95 % CI –6·73, –1·56; P =0·002). A diet characterised by a higher reported intake of n -3 fatty acids, palmitoleic acid (16 : 1) and arachidonic acid (20 : 4 n -6) is associated with a lower AIx in RA patients.